Prevalence and Risk Factors of Women’s Past-Year Physical IPV Perpetration and Victimization in Tanzania - Reese, Bianka M. (Journal of interpersonal violence, 2021)
Recent studies of intimate partner violence (IPV) in high-resource countries suggest that men and women may perpetrate similar rates of violence against their partners, yet the prevalence and etiology of female-perpetrated IPV, especially in comparison with IPV victimization among females, remains largely understudied in low-resource, high-prevalence countries, particularly in sub-Saharan Africa. Using multivariate logistic regression models, the current study examines the prevalence of and risk factors associated with past 12-month experiences of isolated physical IPV perpetration (i.e., violence perpetrated against an intimate partner not in self-defense) and physical IPV victimization among a nationally representative sample of women of reproductive age (15-49 years) from Tanzania who completed the Tanzanian Demographic and Health Survey Domestic Violence Module (n = 5,372). Approximately 1.5% reported perpetrating violence in the past 12 months, whereas 35% reported victimization in the same time period. Risk factors of past 12-month IPV perpetration included past 12-month IPV victimization, making cash or in-kind earnings, having autonomy in decision making, and acceptance of justifications for wife beating. Women much younger than their partners had lower odds of IPV perpetration. Risk factors of past 12-month IPV victimization included past 12-month IPV perpetration, educational attainment, having children, partner’s alcohol consumption, partner’s decision making, acceptance of justifications for wife beating, and exposure to parental IPV. Making cash or in-kind earnings was the only protective factor against victimization. Findings suggest that female IPV perpetration and victimization may result from a combination of factors including power differentials between partners and attitudes about the acceptability of using violence. Future research directions and implications for policy and prevention efforts to reduce IPV in Tanzania are discussed.